WTO Subsidies Agreement on Fisheries (2022-2024): Agreed Terms and Implications for Indonesia - Mucharom, Rully Syahrul; Suriaamadja, Toto Tohir; Januarita, Ratna; Jaya, Belardo Prasetya Mega; Maharani, Dwi Gita; Asari Taufiqurrohman (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Indonesia has issued a fisheries subsidy policy to encourage the development of the fishing industry because this sector contributes to national development, but the subsidies applied must be in accordance with the provisions stipulated in the WTO. Indonesia is a member of the WTO and in the last few meetings held by the WTO in which the WTO prohibits subsidies, besides that fisheries subsidies can cause depletion of fish stocks and damage to marine biota. This is not in line with the UN program, namely Sustainable Development related to sustainable fisheries, so the implementation of fisheries subsidy policies can cause problems. the 12th WTO ministerial conference, a draft was drafted, but until now the draft has not been ratified, the draft fisheries subsidies at the WTO specifically regulate fisheries subsidies that are prohibited and exceptions in general. the 13th Ministerial Conference 2024 has not yet concluded negotiations on agricultural and fisheries subsidy issues, which remain key concerns for the conference organizers. Trade or Economic Ministers of the WTO engaged in negotiations are aware of the significant differences in positions among member states, necessitating further time for additional negotiations to be continued by permanent delegations in Geneva. The impact of the draft WTO fisheries subsidy, if successfully ratified, will have a negative impact on Indonesia in terms of the fishery market, fishery resources and employment.